Animal carcass- and wood-derived biochars improved nutrient bioavailability, enzyme activity, and plant growth in metal-phthalic acid ester co-contaminated soils: A trial for reclamation and improvement of degraded soils. (1st May 2020) - Chen, Hanbo; Yang, Xing; Wang, Hailong; Sarkar, Binoy; Shaheen, Sabry M.; Gielen, Gerty; Bolan, Nanthi; Guo, Jia; Che, Lei; Sun, Huili; Rinklebe, Jörg
Abstract: Reclamation of degraded soils such as those with low organic carbon content and soils co-contaminated with toxic elements and phthalic acid esters (PAEs) is of great concern. Little is known about the efficiency of plant- and animal-derived biochars for improving plant growth and physicochemical and biological properties of co-contaminated soils, particularly under low content of organic matter. Hence, a pot trial was carried out by growing pak choi ( Brassica chinensis L.) to assess the influence of different doses (0, 0.5, 1, 2, and 4%) of animal (pig carcass) and wood ( Platanus orientalis ) derived biochars on soil properties, nutrient availabilities, plant growth, and soil enzyme activities in two soils containing low (LOC) and high (HOC) organic carbon contents and co-contaminated with di-(2-ethylhexyl) phthalic acid (DEHP) and cadmium (Cd). Biochar applications improved pH, salinity, carbon content, and cation exchange capacity of both soils. Addition of biochars significantly increased the bioavailability and uptake of phosphorus and potassium in the plants in both soils with greater effects from pig biochar than wood biochar. Biochar additions also significantly enhanced urease, sucrase, and catalase activities, but suppressed acid phosphatase activity in both soils. The impact of pig biochar was stronger on urease and acid phosphatase, while the wood biochar was more effective with sucrase and catalase activities. The biomass yield of pak choi was significantly increased after biochar addition to both soils, especially in 2% pig biochar treatment in the LOC soil. The positive response of soil enzymes activities and plant growth for biochar addition to the Cd and DEHP co-contaminated soils indicate that both biochars, particularly the pig biochar can mitigate the risk of these pollutants and prove to be eco-friendly and low-cost amendments for reclaiming these degraded soils. Graphical abstract: Image 1 Highlights: 2% pig biochar addition increased the yield of pak choi. Pig biochar improved nutrient phytoavailabilities more than wood biochar. Tested biochars enhanced soil urease, sucrase and catalase activities. Biochars had prominent influence on pak choi growth in low organic carbon soil.